RF Modelling and Characterization of Tyre Pressure Sensors and Vehicle Access Systems - Brzeska, Malgorzata Dominika (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2015)
Core topics of the work are the vehicle access systems such as PAssive Start and Entry (PASE), Remote Keyless Entry (RKE) as well as Tyre Pressure Monitoring System (TPMS). Two goals are followed: the development of antennas and functionality analysis from RF (Radio Frequency) point of view and improvement of system parts. The overall objective of this work is to advance the state-of-the-art vehicular electromagnetic simulation taking into account the vehicle body and nearest surroundings.